Leadership and the everyday practice of Consultant Radiographers in the UK: Transformational ideals and the generation of self-efficacy. Issue 2 (May 2017) - Booth, L.; Henwood, S.; Miller, P.K.
Abstract: Introduction: This paper outlines findings from a broader, two-year project investigating the role of Consultant Radiographers (CRs) in the UK, focussing specifically on the leadership aspect of that role. Methods: Using a qualitative-thematic approach, the leadership-related experiences of a purposive sample of six participating CRs are explored, alongside the systems through which they evaluated how successful they had been as leaders. Results: It is evidenced that many of the ways in which participants describe their own leadership practice, particularly in the intra-team domain, is consistent with the precepts of the Transformational Leadership Model. For example, they highlight how they have asserted positive influence and encouraged collective action and decision-making. However, the experiential focus of the analysis reveals that in specific examples of practice, the transformational approach was not always seen as the most useful route to a productive outcome given constrictions on time and other resources within real professional environments. More 'direct' managerial approaches were sometimes deemed necessary, and at others leadership was reduced to simply 'solving other people's problems'. It was also found that the manner in which participants evaluated their own success as leaders was a practical concern, based in part upon having satisfied 'hard' institutional goals, but also on the more personal business of having affirmatively 'surprised' oneself, or a general sense of feeling trusted by colleagues. Conclusion: These findings may help support CRs in the business of real leadership, not least through better understanding how even apparently mundane outcomes can have significant impacts on professional self-efficacy. Highlights: CRs report a rich variety of diverse tasks emerging from their leadership roles. The leadership role is both inward and outward facing. Transformational leadership strategies are often seen as 'ideal' practice. Practical situations often require CRs to find non-transformational 'workarounds'. Personal self-efficacy is a key driver in a CR's sense of leadership capacity.